Kemandirian Belajar Siswa SMP melalui Model Problem Based Learning (PBL) - Faurina Rinanda (Universitas Syiah Kuala, 2019)
Abstract. Learning autonomy of Indonesian students is relatively low because, during the learning, the teacher directly explained the materials and solved the example problem without involving the students. This situation led to students being less engaged and independent. Therefore, we need an effort to improve student learning autonomy; one of them is using the Problem Based Learning (PBL) learning model. This study was aiming at determining the learning autonomy of students who were taught using the PBL learning model and those learned in conventional learning. This study was an experimental study with a pre-test post-test control group design. The population were all Year 7 students of one of the junior high schools in Banda Aceh, and two classes were selected as the samples randomly. The instrument was a student learning autonomy questionnaire. Data were analysed using t-test and two-way ANOVA to examine the differences in the improvement of students between levels. The results revealed that the students’ learning autonomy in mathematics during the learning with the Problem Based Learning (PBL) model was better than their counterparts. There was also no interaction between the Problem Based Learning (PBL) learning model and student level (high, medium, low) on student learning autonomy.Keywords: Students’ Learning Autonomy, Problem Based Learning (PBL) Model.